Pengembangan Bahan Ajar Multimedia Interaktif pada Praktikum Titrasi Asam Basa - Peri Oktiarmi; Muhammad Rusdi; Asrial Asrial (Universitas Jambi, 2014)
The objective of the research is to develop a class xi chemistry instructional medium the topic of acid-base titration with the orientation of improving the students skill of scientific process in the laboratory. The research is a developmental research and the model used is ADDIE, which stand for Analyze, Design, Develop, Implement and Evaluate. Having been validated by some assessors and teachers, the medium developed proves adequate and can be implemented among class xi high school students. The result of the reaserch show that the student respon well to the implementation of the medium. The medium can be used by student with various capabilities : however, among weak students teacher’s guidance is needed.